O paradoxo a partir da teoria dos blocos semânticos : língua, dicionário e história - Machado, Julio Cesar (2015)
In general, the idea of this work is to investigate the paradox, our object, by a linguistic and argumentative way, from the Theory of Semantic blocks (TBS). And specifically, for this, we adopted as main methods, two gestures: the relationship between linguistic elements as analysis condition, on the one hand, and the interdependence of its structure and significance, on the other hand, both in the non- use (language) and the use of language (enunciation). This second method of interdependence, when applied to our object, the paradox, becomes our first central hypothesis, the possibility of semantic paradox: the strange and difficult linguisticargumentative consideration of opposite significances, but in the interdependent state. And in this context we will also develop a second central hypothesis: the argumentative cube, while theoretical actualization of the argumentative square (the basic theoretical framework of our theory). Organizationally, the resourcefulness of this work will be carrying out in several specific strands, distributed throughout the chapters, namely: theory / paradox (divided into "Argumentation in the Language" / paradox, at first, and "Theory of Semantic Blocks "/ paradox, in a second stage); discours / paradox; dictionaries / paradox; "Historic Semantics of Enunciation" / paradox; relationship between languages / paradox and anteriority / paradox. In addition to these relational axes established to better observe our object, the paradox, and defend our hypothesis, the semantic paradox, we elected as central corpora, a group of dictionaries in which we can catch "which is said to be" a paradox and "as they say "a paradox to ponder" which means "a paradox. These dictionaries are divided into main corpus: Dictionnaire Historique de langue francaise, and and secondary corpora : Enciclopédia e Dicionário ilustrado, Kokugo Ziten e Dicionário Houaiss da Língua Portuguesa, among others.